Nilai-Nilai Pendidikan Tasawuf dalam Film “99 Kali Rindu” Karya Azhari Zain - Aldin, Fahri; Sahal, Yosep Farhan Dafik (Bestari, 2020)
This study aims to (1) determine the meaning of Sufism education; (2) knowing the values ​​of Sufism education contained in the film "99 Kali Rindu"; (3) to determine the relevance of the values ​​of Sufism education in the film "99 Kali Rindu" with Islamic education today. The method used in this data analysis is descriptive analysis method, while the data collection techniques used in this data collection are documentation techniques and library research. The collected data were then analyzed by unit processing. In the film 99 Kali Rindu, after doing the research it can be concluded that: (1) the definition of sufism is the teaching or belief that knowledge of truth and Allah can be achieved by means of mental vision of reflection, (2) the film has sufism educational values ​​that can be applied to students. these values ​​are: (a) divine value (deity), (b) insaniyah (human) values, (c) natural value (nature), (3) the relevance of sufism education in islamic education is that it has a relevant relationship, which is applied to schools and educational institutions. The dialogue excerpt made by Azhari Zain in his film 99 Kali Rindu, contains the values ​​of Sufism education which are in accordance with the material taught at schools and educational institutions such as Akidah Akhlak, Al-Quran Hadith, and other Islamic education. The values ​​in it are very important to be instilled in students, so that they can become a generation that fights for and advances this nation with knowledge and morals